ANALISIS PENGUKURAN KINERJA MANAJEMEN RANTAI PASOK DENGAN METODE SUPPLY CHAIN OPERATION REFERENCE (SCOR) PADA PT SEMEN TONASA - herliana (Scientia integritas Utama, 2022)
This research aims to see and measure the performance of the supply chain management implemented by PT Semen Tonasa in Pangkep. This research was conducted based on the Supply Chain Operation Reference (SCOR) method using primary data. The Supply Chain Operation Reference (SCOR) method is based on five components, namely reliability, responsiveness, flexibility, cost, and assets that are assessed and tested whether they are aligned or not as the best way to achieve business goals. It is found that Perfect order fulfilment (POF), Order fulfillment cycle time (OCFT), Upside supply chain flexibility (USCF), Supply chain management cost (SCMC) dan Cost of good sold (COGS) were in high level of performance (excellent positions) with a gap value of 0%, 0%, 0%, 20% and 3% respectively. Meanwhile Return on supply chain fixed asset (ROFA) and Return on working capital (ROWC) re only in a moderate level by indicating result (gap value) around 10% and 9% respectively. It is, however, Cash to cash cycle time (CTCCT) still in the average position with a gap value of 0%. It can be concluded that all supply chain components have been manage properly.